Korelasi Indeks Eritrosit Dan Red Cell Distribution Width (RDW) Pada Pasien Gagal Ginjal Kronik di Instalasi Hemodialisa RSUD Bahteramas - Bonni Rubak; Susanti; Reymon; Sendy Ramadhany (Jurnal Analis Kesehatan Kendari, 2025)
Chronic kidney failure (CKD) is a disease condition that progressively occurs with a slow decline in kidney function that cannot return to normal, so that in advanced stages it requires replacement therapy such as hemodialysis. One of the most common complications in patients with CKD is anemia. This anemia is usually caused by reduced production of erythropoietin hormone which causes a shortening of erythrocyte lifespan. To evaluate the characteristics of anemia in chronic kidney failure (CKD) patients, hematological examination of erythrocyte indices, including Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH), and Mean Corpuscular Hemoglobin Concentration (MCHC), as well as Red Cell Distribution Width (RDW), are performed. This study aims to determine the correlation between erythrocyte indices (MCV, MCH, and MCHC) and Red Cell Distribution Width (RDW) in CKD patients undergoing hemodialysis at Bahteramas Hospital. The study was conducted descriptively analytically with accidental sampling method of 77 CKD patients. The results of statistical analysis using the chi-square test showed a significant value in the MCV examination and RDW value of 0.000 under the p value <0.05, MCH examination and RDW value found a significant value of 0.000 under the p value <0.05, and MCHC examination and RDW value found a significant value of 0.000 under the p value <0.05. This shows that there is a statistically significant relationship between erythrocyte index and RDW value in CKD patients in the Hemodialysis Installation at Bahteramas Hospital.